DAMPAK KEPEMIMPINAN DIRI TENAGA OPERASIONAL TERHADAP PENINGKATAN KINERJA (SURVEY PADA PT. TRANSPOWER MARINE, TBK 2015) - Andi Prasetiawan (Dinamika Bahari, 2017)
The research aim to now relation leadership of x'self with operational energy performance In this research, target population (target) is all PT. Transpower Marine,Tbk employees while population reached by is all PT. Transpower Marine operational energy, Tbk in this case counted 40 crew man. Research Sampel of is set in this research is saturated sampel counted 40 People. Technique analyse data use regresi analysis and simple correlation. Pursuant to examination of conducted research hypothesis, hence this research indicate that fourthly of hypothesis which is raised in this research (H1) accepted and refuse hypothesis zero (Ho). (1) There are positive relation between leadership of x'self (X) with operational energy performance,.